2021
DOI: 10.3389/fmicb.2021.778968
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous and Endogenous Phosphoethanolamine Transferases Differently Affect Colistin Resistance and Fitness in Pseudomonas aeruginosa

Abstract: Colistin represents a last-line treatment option for infections caused by multidrug resistant Gram-negative pathogens, including Pseudomonas aeruginosa. Colistin resistance generally involves the modification of the lipid A moiety of lipopolysaccharide (LPS) with positively charged molecules, namely phosphoethanolamine (PEtN) or 4-amino-4-deoxy-L-arabinose (Ara4N), that reduce colistin affinity for its target. Several lines of evidence highlighted lipid A aminoarabinosylation as the primary colistin resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Cervoni et al also demonstrated that MCR-1 increases colistin resistance in recipient cells. Moreover, the expression of MCR-1 in Pseudomonas does not affect bacterial growth or cell envelope homeostasis (Cervoni et al, 2021).…”
Section: The Epidemiology Of the Mcr Gene Inmentioning
confidence: 99%
“…Cervoni et al also demonstrated that MCR-1 increases colistin resistance in recipient cells. Moreover, the expression of MCR-1 in Pseudomonas does not affect bacterial growth or cell envelope homeostasis (Cervoni et al, 2021).…”
Section: The Epidemiology Of the Mcr Gene Inmentioning
confidence: 99%
“…Except for pMEimuBC, the overexpression of all DNA polymerases inhibited the growth of HolD-depleted cells with respect to the empty plasmid controls, and none of them rescued the growth of HolD-depleted RecA-deficient cells (Figure S4). The inhibitory effect of polymerase-expressing constructs was also observed in HolD-depleted cells cultured without IPTG (Figure S4), plausibly because of leaky gene expression from the pME6032 plasmid in the absence of the inducer [57]. This effect appears to be dependent on HolD depletion, as the overexpression of the DNA polymerases marginally affected the growth of wild-type and ∆recA cells (Figure S4).…”
Section: Homologous Recombination Is Essential For Hold-depleted P Ae...mentioning
confidence: 80%
“…However, these approaches are time-consuming and require a hard-to-achieve standardization process to ensure similar gene expression and active protein levels. Moreover, it has been shown that heterologous overexpression of P. aeruginosa eptA (Cervoni et al, 2021) or dysregulation of S. Typhimurium eptA transcription (Vaara et al, 1981;Olaitan et al, 2014) lead to colistin resistance. Hence, the identification of other bioinformatic criteria that can be used to discriminate between mcr and eptA can improve the ability to detect colistin resistance genes in bacterial WGS data and provide an important basis for selecting genes for phenotypic characterization.…”
Section: Evolution and Diversification Of Mcr Is The Results Of A Mul...mentioning
confidence: 99%
“…However, these approaches are time-consuming and require a hard-to-achieve standardization process to ensure similar gene expression and active protein levels. Moreover, it has been shown that heterologous overexpression of P. aeruginosa eptA (Cervoni et al, 2021) or dysregulation of S . Typhimurium eptA transcription (Vaara et al, 1981; Olaitan et al, 2014) lead to colistin resistance.…”
Section: Discussionmentioning
confidence: 99%